THE INFLUENCE OF HALOKINESIS ON GAS-AND-OIL PRESENCE OF THE DNIEPER-DONETSK DEPRESSION - KURYLENKO, V.; PETROVA, E.; HUSYNINA, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The description of galokinesis as a solid flow of salt is presented and notion such terms as viscosity and rheidity. High plasticity and low salt density are the reason of convective instability of sedimentary bulk. Vibration forces and deep fluids influence on the salt flows. Galokinesis of upper-Devonian salt governs the structure map of oversalt deposits and oil-gas content of the Dnieper-Donetsk depression.